Evaluation of the Impact of Saara w.s.r to Obesity and Its Ayurvedic Management: A Retrospective Analysis (International Journal of Ayurveda and Pharma Research, 2024)
Obesity, the name itself causes a social as well as mental trauma for the individuals suffering from it. Although in the initial stage of the disease, the individuals overlook the problem, but later, it becomes the cause of much other upbringing disease. So the question arises, what is the cause of the sudden rise in obesity? Does it relate only to the lifestyle disorder or there is a genetic makeup in an individual, in which the tissues starts proliferating and storing adipose tissue, when it gets any favourable condition and environment. In Ayurveda, the genotype and the phenotype has been explained in the term of Saara (essence). Therefore an attempt has been made to understand the effect of Saara. Materials and Methods: 124 case papers diagnosed with obesity and had undergone any Panchakarma treatment at KLEU Shri BMK Ayurveda hospital, Belgaum, Karnataka, India. Complete before and after assessment of total cholesterol, HDL, LDL, triglyceride, circumference measurement, BMI, weight. Result: In Medosaara population and in Mamsasaara individuals, significant decrease observed in total cholesterol (3.76%) and mid- abdomen circumference (34.97%), and triglyceride (10.3%), LDL (6.52%), Mid-thigh circumference (7.36%), abdominal circumference (7.11%), and BMI (6.73%). Conclusion: The Saara of any individual determines the possible outcome of any disease, irrespective of the treatment the individual is undergoing. Therefore, in this study of obesity, it was concluded that Medosaara individuals has significant weight reduction from the baseline.